2006
DOI: 10.4049/jimmunol.177.5.3201
|View full text |Cite
|
Sign up to set email alerts
|

Leukotrienes Are Essential for the Control ofLeishmania amazonensisInfection and Contribute to Strain Variation in Susceptibility

Abstract: Leukotrienes (LTs) are known to be produced by macrophages when challenged with Leishmania, but it is not known whether these lipid mediators play a role in host defense against this important protozoan parasite. In this study, we investigated the involvement of LTs in the in vitro and in vivo response to Leishmania amazonensis infection in susceptible (BALB/c) and resistant (C3H/HePAS) mice. Pharmacologic or genetic deficiency of LTs resulted in impaired leishmanicidal activity of peritoneal macrophages in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
87
0
4

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(94 citation statements)
references
References 52 publications
3
87
0
4
Order By: Relevance
“…Other works have shown that apoptosis triggered after activation of the P2X7 receptor is dependent on PLA 2 and 5-LO (24). Based on these findings and on data indicating that LTB 4 reduces the parasitic load of infected macrophages (20), we examined whether the ATPe-induced release of LTB 4 requires the P2X7 receptor. Our data demonstrate that ATP was able to induce LTB 4 production.…”
Section: Atp Induces Release Of Ltb 4 In Macrophages After P2x7 Recepmentioning
confidence: 99%
See 2 more Smart Citations
“…Other works have shown that apoptosis triggered after activation of the P2X7 receptor is dependent on PLA 2 and 5-LO (24). Based on these findings and on data indicating that LTB 4 reduces the parasitic load of infected macrophages (20), we examined whether the ATPe-induced release of LTB 4 requires the P2X7 receptor. Our data demonstrate that ATP was able to induce LTB 4 production.…”
Section: Atp Induces Release Of Ltb 4 In Macrophages After P2x7 Recepmentioning
confidence: 99%
“…Serezani and coworkers (20) demonstrated that 5-LO participates in the elimination of L. amazonensis. Therefore, we investigated the importance of 5-LO in reducing the parasite load triggered by ATPe.…”
Section: -Lo Is Important In the Decrease Of Parasite Load Mediated mentioning
confidence: 99%
See 1 more Smart Citation
“…major (AFONSO e SCOTT, 1993), e os mecanismos que determinam maior sucesso no combate à infecção não estão completamente esclarecidos (SEREZANI et al, 2006 …”
Section: O Sistema Imune E a Infecção Por Leishmaniaunclassified
“…LTs regulam a resposta imune protetora, quer seja do padrão T H 1 ou do T H 2, em infecções como aquelas por K. pneumoniae [61] , H. capsulatum [54] , Strongyloides venezuelensis [68] , Leishmania amazonensis [69] . Neste contexto, mostramos que a infecção pelo Mtb induz produção de LTB 4 nos pulmões, persistente até pelo menos 60 dias após a infecção, sendo esta importante para o desenvolvimento de resposta protetora do hospedeiro [70] .…”
Section: Mediadores Lipídicos Como Moduladores Da Resposta Imuneunclassified